Tinjauan Maslahah Mursalah terhadap PERMA No. 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana - Aisyah Rossyta Dewia; Fery Dona (Universitas Sebelas Maret, 2022)
Dispute resolution through the judicial process is considered ineffective and efficient, because it is slow and convoluted. This is not in accordance with the basic principles in the judiciary, namely the judiciary is carried out in a simple, fast and low cost way. However, with the establishment of PERMA No. 2 of 2015 concerning Procedures for Settlement of Simple Lawsuits, the settlement of simple lawsuits disputes through Litigation can run more efficiently with all the provisions contained therein, including the elimination of exceptions. This study uses a literature study research method with a normative juridical approach. The data obtained from primary and secondary legal materials were collected using the library method for further analysis to determine the urgency of removing exceptions in PERMA No. 2 of 2015 concerning Procedures for Settlement of Simple Lawsuits. Based on the analysis carried out, the elimination of exceptions in the regulation is in accordance with the principles of simplicity, speed and low cost in court. Where this principle aims to make it easier for people to find the truth without injuring the rights of the parties because the entire process to be carried out has been explained in advance by the judge. In this case, it also avoids procrastination by the parties so that disputes can be resolved more quickly. Eliminating this exception is in line with the goal of maslahah mursalah. Because the purpose of maslahah mursalah with the use of simple, fast and low-cost principles is the same, namely for benefit by providing convenience in seeking the truth.